A survey of ab-initio calculations shows that segregation-induced grain boundary embrittlement is predicted by bond-breaking arguments. (1st March 2016) - Gibson, Michael A.; Schuh, Christopher A.
Abstract: The segregation of solute atoms to grain boundaries can have a large influence on the mechanical behavior of polycrystals, particularly in metallic alloys. An overview of 400 calculations of solute-induced changes in grain boundary cohesion from 81 separate studies quantitatively demonstrates that the majority of the variation in solute-induced changes in boundary cohesion is explained by simple bond-breaking arguments. This trend is robust to changes in crystal structure and computational methods. The secondary contributions to embrittlement from other mechanisms, such as atomic size effects and charge transfer, are quantified and discussed as well. Graphical abstract: